Do statins improve outcomes for patients with non-small cell lung cancer? A systematic review and meta-analysis protocol. Issue 9 (10th September 2018) - Li, Feng; Liu, Guangyu; Roudi, Raheleh; Huang, Qi; Swierzy, Marc; Ismail, Mahmoud; Zhao, Song; Rueckert, Jens-Carsten
Abstract : Introduction: Lung cancer is the most common neoplasm and the leading cause of cancer-related death worldwide. Non-small cell lung cancer (NSCLC), accounting for 85% of all lung cancer cases, is frequently diagnosed at an advanced and metastatic stage. In addition, survival of patients with NSCLC has not improved significantly over the recent decades. Statins are used as a cholesterol-lowering agent, but recently preclinical and clinical studies have revealed their anticancer effects. Thus, this systematic review and meta-analysis aims to clarify whether statins improve the prognosis of patients with NSCLC. Methods and analysis: We will search MEDLINE (PubMed), EMBASE, Web of Science, the Cochrane Central Register of Controlled Trials and ClinicalTrials.gov with no restriction on language. Both randomised controlled trials (RCTs) and observational cohort studies evaluating the prognostic role of statins in patients with NSCLC will be included. The primary outcome will be overall survival, and the secondary outcomes will include cancer-specific survival, disease-free survival and cancer recurrence. Two assessors will assess the RCTs using the Cochrane Collaboration's risk of bias tool and the observational cohort studies according to ROBINS-I. Publication bias will be assessed by funnel plot using the STATA software v.13.1. Ethics and dissemination: No ethical issues are predicted. This systematic review and meta-analysis aims to describe the prognostic effects of statins in patients with NSCLC, which would help clinicians to optimise treatment for patients with NSCLC. These findings will be published in a peer-reviewed journal and presented at national and international conferences. PROSPERO registration number: CRD42016047524.